2019
DOI: 10.1152/ajpheart.00370.2019
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of chemotherapy on human coronary microvascular function

Abstract: Chemotherapy (CT) is a necessary treatment to prevent the growth and survival of cancer cells. However, CT has a well-established adverse impact on the cardiovascular (CV) system, even years after cessation of treatment. The effects of CT drugs on tumor vasculature have been the focus of much research, but little evidence exists showing the effects on the host microcirculation. Microvascular (MV) dysfunction is an early indicator of numerous CV disease phenotypes, including heart failure. The goal of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Cardiac mass showed a significant decrease (p < 0.05) following 4 months of treatment, and echocardiographic metrics also showed that after the 4 month treatment, there was a significant (p < 0.05) decrease in the ventricular septum thickness in treated compared to untreated mice. Recent clinical studies have indicated that reduced myocardial capillary density (microvascular rarefaction) with reduced coronary flow reserve (maximum increase in blood flow through the coronary arteries above the normal resting volume) contributes substantially to diastolic dysfunction in HFpEF patients [28,29]. The observation of subclinical cardiotoxicity in DOX/TRZ treated mice is consistent with the observation that cardiac ECs, in addition to cardiomyocytes became damaged during the combination treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Cardiac mass showed a significant decrease (p < 0.05) following 4 months of treatment, and echocardiographic metrics also showed that after the 4 month treatment, there was a significant (p < 0.05) decrease in the ventricular septum thickness in treated compared to untreated mice. Recent clinical studies have indicated that reduced myocardial capillary density (microvascular rarefaction) with reduced coronary flow reserve (maximum increase in blood flow through the coronary arteries above the normal resting volume) contributes substantially to diastolic dysfunction in HFpEF patients [28,29]. The observation of subclinical cardiotoxicity in DOX/TRZ treated mice is consistent with the observation that cardiac ECs, in addition to cardiomyocytes became damaged during the combination treatment.…”
Section: Discussionsupporting
confidence: 71%
“…[31] This finding highlights that MVN functionality, even in healthy vessels, is altered during and following successive rounds of treatment, which can recapitulate the adverse effects of chemotherapy often inferred, [32] and directly shown recently in ex vivo microvasculature. [33] Next, we compared drug delivery between a simple spheroid model and our system. Taxol was used to treat TSs alone and within vascular networks (TS-MVN) ( Figure 4C-G).…”
Section: Vascular Transport Of Chemotherapeutics In 3dmentioning
confidence: 99%
“…(reviewed by Armenian et al 19 ). Our recent study showing that anthracycline exposure causes a loss of endothelial dilator function in the human coronary circulation further amplifies the negative impact of different cancer therapies on vascular function 20 …”
Section: Discussionmentioning
confidence: 82%